The effect of grit on L2 willingness to communicate among Chinese junior high school students: an analysis of the differential roles of foreign language enjoyment and anxiety - Li, Gengchun (Frontiers in Psychology, 2024)
With the burgeoning research on positive psychology, grit has gradually attracted scholarly attention in the field of L2 acquisition, and it has been shown to be a significant positive predictor of L2 achievements and outcomes. However, despite being an important factor in L2 acquisition, grit has rarely been incorporated as a research variable in prior research on willingness to communicate in a second language (L2 WTC), especially among Chinese teenagers who find themselves in a foundational stage of developing their L2 communicative competence. Based on a survey among 238 Chinese junior high school students, this study analyzed the effect of their grit on their L2 WTC, and explored the differential roles of foreign language enjoyment (FLE) and anxiety (FLA) in their interactions. The results revealed that: (1) perseverance of effort (PE), consistency of interest (CI) and FLE had significantly positive correlations with L2 WTC, whereas FLA was found to have a significantly negative correlation with L2 WTC; (2) PE and CI served as significant positive predictors of L2 WTC; (3) FLE mediated the interactions between PE and L2 WTC and between CI and L2 WTC, while the mediating effects of FLA were found to be statistically non-significant. The findings can provide theoretical implications for furthering L2 WTC research, as well as practical reference for its development among Chinese junior high school students.